ChemInform Abstract: A New Cobalt—Salen Catalyst for Asymmetric Cyclopropanation. Synthesis of the Serotonin—Norepinephrine Repuptake Inhibitor (+)‐Synosutine. Issue 5 (February 2015) - White, James D.; Shaw, Subrata
Abstract The synthetic value of this protocol is demonstrated by synthesis of (+)‐synosutine (VIII) in five steps from commercially available materials.